Legal Policies for Sustainable Security and Privacy in Big Data and Information sharing- A managerial perspective - Naidu, K. Sowjanya; Chakravarthy, Srinivasa L. (The journal of contemporary issues in business and government, 2021)
Information plays an important role as a resource in the development and success of an organization. It is useful in decision-making to achieve the goals of the organization in an optimized way. This has to be achieved without affecting the information security and privacy of the stakeholders. Organizational policies are addressing the above-stated requirements within the jurisdiction and domain of an organization. While accessing and sharing the information among the organizations, the interests of all the stakeholders across the organizations have to be considered. For this, the policies have to be implemented to safeguard the information of the individuals as well as the organization through regulations or laws. Rapid strides in technology, availability of cheaper computing and networked application environments, high-speed networks, and the increase of data handiness made data sharing very easy across and within the organizations. Data sharing also involves application processing of transactions and analytics in a cloud environment. Sharing in a cloud environment increases the utility but also raises security and privacy issues. Technological changes and domain/legal issues go hand in hand, affecting each other and necessitate changes in laws and regulations. To make the processing of information using big-data and computing infrastructure to be more reliable and secure according to [1] have to be addressed in the design process by considering both technical and legal aspects. Big data processing is not thoroughly vetted for security issues and is posing challenges to the research community. Laws and regulations have not been crystallized. Existing laws related to common issues are being adopted on an ad-hoc basis.With the growing number of breaches unfolding around the nation and the hacking of government websites, the need to create a safe system for all government agencies has never been more critical. This, at best, is a sub-optimal solution as the current laws and regulations may not be appropriate. This article discusses the prevailing issues related to big-data and the laws to protect them. In addition to that, an attempt is made to analyze several Country’s privacy and security laws and regulation which addresses big data security challenges.